Sistema microemulsionado contendo dexametasona com potencial agente para o tratamento da artrite reumatoide - Leite, Joandra Maísa da Silva (2020)
Rheumatoid arthritis (RA) is a chronic systemic rheumatic disease of multiple joints. Dexamethasone (DEXA) is a potent synthetic corticosteroid with anti-inflammatory action used in the treatment of RA. Prolonged use is associated with serious systemic side effects, such as hypertension, hyperglycemia, immune suppression, dependence and resistance. The use of microemulsion (ME) aims to form a system to incorporate DEXA and increase its therapeutic effectiveness. The objective of this work was to develop and characterize an ME containing DEXA for the treatment of RA. Initially, he performed the pre-formulation studies and proceeded with the development of the pseudo-ternary phase diagram (PTPD) to obtain the EM formation region. Analytical validation was performed to quantify DEXA. The systems were characterized in terms of their physical-chemical and morphological aspects using the following techniques: macroscopic aspect, pH, electrical conductivity, refractive index, average droplet size (ADS), polydispersity index (PDI), zeta potential (PZ), polarized light microscopy, rheological measurements, thermogravimetry (TG), differential scanning calorimetry (DSC) and X-ray diffraction (DRX). The preliminary stability of the systems was verified by tests of centrifugation, thermal stress and cooling / heating cycle. Performed an in vitro release test. The PTPD was built using a mixture of surfactants Kolliphor® HS 15 and Span® 60 (9:1), as the oil phase the capric and caprylic acid triglyceride and as the aqueous phase the distilled water. Three formulations were selected (ME-1; ME-2; ME-3). Analytical validation proved to be a specific, exact, precise, robust and fast method. The EE of the systems varied between 88 and 99% and the maximum amount of DEXA incorporated in the systems was 0.06%; 0.29% and 0.36% for ME-1, ME-2 and ME-3, respectively. For macroscopic analysis, liquid, transparent, clear and homogeneous formulations were observed. The pH varied between 5.57 and 6.26 being viable for parenteral administration. The electrical conductivity for ME-1 (135.30 ± 1.66 µS/cm), ME-2 (196.17 ± 1.17 µS/cm) and ME-3 (204.10 ± 1.45 µS/cm) ) suggesting they are O/W type ME. The TMG of the systems varied between 22.25 ± 0.76 and 37.03 ± 1.11 nm confirming that they were MEs. The PDI with values between 0.206 ± 0.007 and 0.314 ± 0.017 suggests having homogeneous droplets. The rheological measurements confirmed the behavior of non-Newtonian fluid of the pseudoplastic type. The DSC revealed an endothermic melting peak at 259.81 °C for DEXA, proving its crystallinity (form B) by the DRX and the formulations showed an amorphous characteristic, suggesting incorporation of DEXA. The systems remained stable in the face of preliminary stability tests. The in vitro release study revealed that in 6 h the release occurred of 54% for ME-3 DEXA 0.08%, and 50% for ME-3 DEXA 0.1%, followed by slow release for up to 72 hours. h, a bust release occurs, followed by a slow and sustained release. Therefore, the proposed microemulsion systems were able to incorporate DEXA, thus being a promising alternative in order to increase the therapeutic efficacy of DEXA.